Remimazolam for anesthesia and sedation in pediatric ambulatory surgery: A scoping review protocol. - Yi Zhang; Linyun Wang; Shuang Guo; Qingjun Zeng; Haishan Cui; Yunbo Mo (PLoS ONE)
Background Remimazolam, an innovative benzodiazepine, exhibits potential for use in anesthesia and sedation for pediatric outpatient procedures, due to its rapid onset, predictable metabolism, and favorable safety profile. While adult studies are increasing, comprehensive evidence for pediatric use remains limited. This scoping review aims to systematically summarize and delineate the existing evidence concerning the application and features of remimazolam in anesthesia and sedation for outpatient pediatric surgical procedures. Objective To systematically map existing evidence on remimazolam use in pediatric ambulatory surgery anesthesia and sedation, identifying key concepts, evidence sources, and knowledge gaps. Methods Following JBI methodology and PRISMA-ScR guidelines, we will search multiple databases, as well as the recommendations provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension tailored for Scoping Reviews (PRISMA-ScR) statement. A comprehensive search will be performed using multiple databases, which include PubMed/MEDLINE, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, CINAHL, Scopus, Google Scholar, along with Chinese databases like the China National Knowledge Infrastructure (CNKI), WanFang Data, and VIP Information.. All published studies on remimazolam use in patients ≤18 years for ambulatory surgery will be included. Two reviewers will independently screen and extract data using a standardized form.